Sleep, bark, or bite: Do natural resources make the difference regarding peaceful or violent conflict?. (March 2020) - Basedau, Matthias; Roy, Vita
Natural resources can create state-based and other conflicts through several causal mechanisms. Debate, however, has remained silent on forms of conflict, especially why violent or peaceful collective action occurs. Combining the literatures on nonviolent- and armed conflict with work on the resource–conflict link, we developed a number of hypotheses on how resources affect the conditions under which collective actors such as ethnic groups remain dormant, voice grievances peacefully or engage in violent rebellion. A grid-cell analysis of ethnic groups in Africa largely confirmed our expectation on the effect of resources. Resource deposits increased the risk that violent conflict would occur; the effect was reversed and ethnic groups become dormant when groups living in resource regions were politically included. We also found some evidence that lootable resources fuel violent but not peaceful conflict. However, the non-resource context best explained the difference between violent and nonviolent conflict. Democracy, political exclusion and geography such as distance from capital and transborder ethnic kin were key in explaining why violent and not peaceful protest emerged. Future research should dig deeper into mechanisms of how resources affect forms of conflict and should further study non-resource conditions that can have functionally equivalent effects.